Sistem Pakar Untuk Mendiagnosis Hama Dan Penyakit Tanaman Padi - Adhinta Nicho Pratama .; Sukadi . (SPEED - Sentra Penelitian Engineering dan Edukasi, 2017)
ABSTRACT – Agriculture has an important meaning for human life, for human life, as long as it is also agriculture will still be there. That's because food is the most basic human needs in addition to air and water. Food is the result of the farm where each year the need for food is increasing as human populations continue to grow. In particular, rice is the result of the rice plant is used as a staple food of man. This often happens, a lot of losses caused due to a plant disease to be diagnosed late and has reached the stage of severe and lead to crop failure.In this study will be an expert system application that provides information on pests and plant diseases can diagnose the symptoms of plant diseases, especially rice, as well as providing a solution to overcome, which will be used to reduce or minimize the risk of crop damage. Implementation of an expert system is built using Microsoft Visual Basic 6.0 and for data storage using microsoft acces 2007.Keywords: Expert System, Disease Diagnosis, System.